EXPLORING THE POSITIVE IMPACT OF CHATGPT ON ENGLISH LANGUAGE LEARNING - Asri Purba; Benedicta Eleanora Putri, Dwi Panggabean, Sandrina Amelia Angelica, Shinta Bella Simanjuntak (Adisam Publisher, 2025)
The study discusses the merits of ChatGPT in the capacity of English Language learners. Research in this context makes use of a quantitative descriptive design where a significant amount of articles and reference material concerning the usage of ChatGPT in context of language learning is collected and critiqued. The study indicates that ChatGPT has a number of positive effects that improve the language skills of the users such as speaking, listening, vocabulary learning and even offering the possibility to give immediate feedback on writing correction. However, it is ChatGPT which also supports and encourages students so that their grammar improves within a short amount of time and it also meets students with individual characteristics. The study concludes emphasizing that ChatGPT is an important rather than a glitch or complication in language learning, at least when the child activities commence.